Exploring the Anticancer Potential of 1,2,4-Triazole Compounds through Molecular Docking Studies - Pratiksha Jadhav (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: This study explores the anticancer potential of 1,2,4-triazole compounds through molecular docking studies. A selection of compounds was docked against cancer-related protein targets, and their binding affinities and interactions were analyzed. Results indicate promising interactions, suggesting potential therapeutic efficacy of these compounds in cancer treatment. Background: The search for novel anticancer agents remains critical due to the limitations of current therapies. 1,2,4-Triazole compounds have shown promise in medicinal chemistry, particularly as potential anticancer agents. This study aims to evaluate their efficacy through molecular docking simulations against specific cancer-related protein targets. Methodology: Compounds were selected based on structural diversity and previous reports of bioactivity. Docking simulations were performed using [insert software/tool], employing [mention specific parameters and algorithms]. Protein targets were chosen for their relevance to cancer pathways. Results: Docking results revealed significant binding affinities and interactions between selected 1,2,4-triazole compounds and cancer-related protein targets. Specific interactions, such as hydrogen bonding and hydrophobic interactions, were observed, indicating potential efficacy in disrupting cancer-related pathways.